2019
DOI: 10.20944/preprints201909.0123.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Active Case Finding for Tuberculosis through TOUCH Agents in Selected High TB Burden Wards of Kolkata, India: A Mixed-methods Study on Outcomes and Implementation Challenges

Abstract: Background: Active case finding for TB was implemented in selected sixty high TB burden wards of Kolkata, India. Community volunteers called TOUCH agents (TAs) identified and referred presumptive TB patients (PTBPs) to health facilities for TB diagnosis and treatment. We aimed to describe the ‘care cascade’ of PTBPs identified during July to December, 2018 and to explore the reasons for attrition as perceived by TAs and PTBPs. Methods: An explanatory mixed methods study with quantitative ph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…We believed that case fatality rates could be higher in south Kolkata compared to other parts of KMC due to poor health and hygiene conditions. Additionally, the large parts of east and south Kolkata together with several pockets in slums areas north and west of Kolkata coincided with high TB burden (Figure ; Dey et al., 2019). Studies showed that the TB is associated with a 2.1‐fold increased risk of a severe COVID‐19 disease (MOHFW, 2020).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…We believed that case fatality rates could be higher in south Kolkata compared to other parts of KMC due to poor health and hygiene conditions. Additionally, the large parts of east and south Kolkata together with several pockets in slums areas north and west of Kolkata coincided with high TB burden (Figure ; Dey et al., 2019). Studies showed that the TB is associated with a 2.1‐fold increased risk of a severe COVID‐19 disease (MOHFW, 2020).…”
Section: Resultsmentioning
confidence: 96%
“…Lastly, we have calculated a health and hygiene index to address vulnerable areas where people have the greater likelihood of a weak immune system due to lack of access to clean drinking water, sanitation, and hygiene and thereby increasing the risk of COVID‐19 infections (Das et al., 2020). Such areas are typically prone to greater incidences of TB and other infectious diseases (Dey et al., 2019). Therefore, we have considered the following variables: Percentage of households having drinking water from untreated sources (typically contain pathogens, toxic trace elements such as As, Fe, and Mn, and chances of waterborne viruses, Chakraborti et al., 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large number of patients in private sector has raised concerns about: delayed diagnosis; suboptimal quality of care; incorrect diagnostic treatment protocols; lack of systems for treatment adherence patient support; a high drop-out rate, thus raising the risk of drug resistance to first-line /or second-line drugs 3 . Purba Medinipur with an aim to improve the quality of TB care by introducing innovative solutions [4][5][6][7][8][9] . With the help of THALI project these districts were able to notify nearly 8000 10000 privately treated TB patients respectively during 2017 2018 10,11 .…”
mentioning
confidence: 99%